(untitled) (Bodhi Path, 2023)
Today the life of people is disturbed due to Covid 19 pandemic, whereby So many people have lost their job. The works in offices, companies, factories and shops are closed due to lockdown by the government. The people of all over the world are facing so many problems like constant worry and tension due to lockdown. It is also troubling our peace of mind and forcing us to question our survival. While scientists from all over the world are working hard to unearth medical solutions, thoughts from Buddhism can provide us with a little comfort in our overloaded minds. How we can benefit from the Buddhist principles during these times and after the pandemic time. This is really a testing time for all people of the world. The teachings of the Buddha can help play a major role in current challenging times of fear, anxiety, and isolation to get out of the Covid-19 Pandemic. While Buddhist Principles state that everything is Constantly Changing. As the Buddha’s quote from Dhammapada : sabbē sańkhārā aniccā iti yadā paññāya passati atha dukkhē nibbindati ēsa visuddhiyā maggō All component things, all things that are put together, and all created things are transient, impermanent, and non-constant. When this is often realized through insight, one achieves detachment from suffering. This is the path to total freedom from blemishes. All hardened things are impermanent. (Dhammapada, Chapter XX, verse 277) Whatsoever difficulty we’re facing right now, whatsoever painful emotions we’re experiencing, they will all leave behind because they are impermanent. So powerful Buddhist principles that everything is changing and impermanent. We can say that this terrible period will also pass, and a good time will come when we meet each other without fear. Once again we will arrange parties, meetings, and interactions with students like same before Covid. Buddhist principles can play an important role to build the Post-Covid new normal world order, whereby people across the world live a life without fear and peaceful way. Further, they can help to build friendly relations ties with all the countries in the world, whereby it realizes peace and happiness to the entire world. While the main focus shall be on this research paper, how to create a post-covid new normal world order with the implementation of Buddhist principles. The proposed research paper will elaborate on these points in detail.